The Role of Social Media in Management of Relational Capital in Universities - SmolÄ…g, Klaudia; Åšlusarczyk, Beata; Kot, Sebastian (Prabandhan: Indian Journal of Management, 2016)
Operation of modern organizations is increasingly affected by various solutions in the field of ICT. Mobile technologies, e-learning platforms, or social media stimulate the development of social and economic life. Furthermore, the growing number of Internet users and social media users contribute to the use of potential of these phenomena in the economic activity. Similar tendencies are observed in education. The wide use of ICT tools affects substantial transformations in operation of schools and universities. Particular importance has been attached to cooperation with stakeholders, which, with ICT development, might be extended to a substantially greater scale. The potential of cooperation with stakeholders is termed as relational capital. Nowadays, this capital represents a valuable resource of each organization, since it affects their operation and development. This paper presented the idea of formation of relational capital in universities using social media. Statistical data concerning the use of social media in Poland were presented. Furthermore, key activities connected with the utilization of social media in university operations were indicated. The paper also emphasized the benefits of the use of social media in universities.